OPINION JOURNALISM: THE GENRE OF LITERATURE OR JOURNALISM? - Khorob, S. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article raises the problem of genre and type definition of opinion journalism, its belonging to fiction and journalism. It proves that this creation, coming out of laws of creative work, characterizes activities of both writers and journalists to an equal extent, being on the border in works of belles-lettres and mass media. In addition, the analysis of manifestations of opinion journalism gives grounds to affirm that opinion journalism is not a separate type of literature and not a separate genre of journalism. It is rather the system of genres among major forms that are inherent in literary-fictional and journalistic creative work.